(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Anumber of data mining algorithms have been introduced to the community thatperform summarisation and classification of data with respect to a targetattribute, deviation detection, and other forms of data characterisation andinterpretation. One popular summarisation and pattern extraction algorithm isthe association rule algorithm. Association rule is described as anassociational relationship between a group of objects in a transactionaldatabase [Zhang S. et.al., 2006]. The following discussion shall be useful toJustify the intervention of human heuristics in the data mining process.